The Descent of Man and Selection in Relation to Sex, Vol. II (1st Edition) - Darwin, Charles, 1809-1882 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Descent of Man, and Selection in Relation to Sex, Vol. II (1st Edition)" by Charles Darwin is a book published in 1871. This groundbreaking work applies evolutionary theory to human origins and introduces sexual selection as a driving force in biological adaptation. Darwin examines mental and physical traits, comparing humans to animals, and explores controversial topics including racial differences, gender roles, mate choice, and the impact of civilization on natural selection. The book challenged Victorian society's assumptions about human uniqueness and sparked debates about morality, progress, and humanity's place in nature. (This is an automatically generated summary.)
Transcription of 1871 edition.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Descent_of_Man,_and_Selection_in_Relation_to_Sex
Release date is 2011-06-25
E-text prepared by Steven Gibbs, Turgut Dincer, and the Online Distributed Proofreading Team
Keywords: Evolution (Biology); Human beings -- Origin; Sexual selection in animals; Sexual dimorphism (Animals); Sex differences